Joined body manufacturing method, metallic paste, and method for producing the same
Patent Information
- Application Number
- JP2023125504
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-01
- Publication Date
- 2025-02-14
AI Technical Summary
【0014】 本発明によれば、金属ペーストを用いる接合体の製造において、部材の脱落を充分抑制することができる接合体の製造方法、並びに、そのような方法に用いることができる金属ペースト及びその製造方法を提供することができる。
Smart Images

Figure 2025021643000006 
Figure 2025021643000001 
Figure 2025021643000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing a bonded body, a metal paste, and a method for producing the same. [Background technology]
[0002] When manufacturing semiconductor devices, various bonding materials are used to form a bonding layer that bonds a semiconductor element to a lead frame or the like (supporting member). For example, high-lead solder has been used to form a bonding layer for bonding power semiconductors, LSIs, and the like that operate at temperatures up to about 150°C. In recent years, semiconductor elements have become higher capacity and more space-saving, and there is an increasing demand for semiconductors to operate at high temperatures of 175°C or higher. In order to ensure the operational stability of such semiconductor devices, the bonding layer needs to have high connection reliability and high thermal conductivity. However, in the temperature range of 175°C and above, the bonding layers of the high-lead solder and lead-free solder that have been used in the past have issues with connection reliability and also have insufficient thermal conductivity (30 Wm -1 K -1 ) therefore alternative materials are needed.
[0003] As one of the bonding methods using alternative materials, a bonding method utilizing the low-temperature sintering phenomenon of copper fine particles has been proposed. The sintered copper layer formed by this method has excellent mechanical strength, and connection reliability at high temperatures can be easily obtained, and material costs can be kept low. As such a sintered copper layer, a sintered copper layer obtained by reducing and sintering copper oxide particles has been proposed (see Patent Document 1 and Non-Patent Document 1 below). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Patent No. 5006081 [Non-patent literature]
[0005] [Non-Patent Document 1] T. Morita, Y. Yasuda: Materials Transactions, 56(6), 2015, 878-882 [Non-Patent Document 2] JHHildebrand et al., The Solubility of Non-Electrolytes, Interscience, 1950 Summary of the Invention [Problem to be solved by the invention]
[0006] A power module or the like in which a support member and a semiconductor element are bonded via a sintered copper layer is usually manufactured through the following process. First, a copper paste in which copper particles are dispersed in a liquid dispersion medium is prepared, and this copper paste is applied to a support member to form a coating of the copper paste. Next, a semiconductor element is placed on the copper particle-containing layer formed by drying the coating. The laminate thus obtained is transported to a sintering furnace or the like, and the copper particle-containing layer is sintered to bond the support member and the semiconductor element.
[0007] Conventional copper pastes, when dried, are difficult to obtain the property (hereinafter also referred to as tackiness) that allows them to temporarily attach semiconductor elements, etc. If the semiconductor elements fall off during transportation of the laminate, this leads to a decrease in yield in the manufacture of joined bodies such as power modules.
[0008] Therefore, an object of the present invention is to provide a method for manufacturing a joined body that can sufficiently suppress the falling off of components when manufacturing a joined body using a metal paste, as well as a metal paste that can be used in such a method and a method for manufacturing the same. [Means for solving the problem]
[0009] The present invention relates to the following [1] to
[13] .
[0010] [1] A method for producing a joined body, comprising: a first step of applying a metal paste containing metal particles and a liquid dispersion medium that is liquid at 25°C onto a first component to form a coating of the metal paste; a second step of removing a portion of the liquid dispersion medium from the coating to form a metal particle-containing layer; a third step of placing a second component on the metal particle-containing layer to obtain a laminate; and a fourth step of sintering the metal particle-containing layer of the laminate, wherein droplets are generated on the surface of the metal particle-containing layer in the second step. [2] The method for producing a joined body according to [1], wherein the liquid dispersion medium contains a first compound and a second compound having a lower boiling point and a smaller SP value than the first compound, and the metal paste contains a third compound having a smaller SP value than the second compound. [3] The method for producing a joined body according to [1], wherein the liquid dispersion medium contains a polyether alcohol compound and an alcohol compound having a boiling point lower than that of the polyether alcohol compound and having a hydrocarbon group having 8 or more carbon atoms, and the metal paste contains a fatty acid having 10 or more carbon atoms. [4] The method for producing a bonded body according to any one of [1] to [3], wherein the metal particles contain sub-micro copper particles, spherical micro copper particles, and flake-shaped micro copper particles. [5] The method for producing a bonded body according to any one of [1] to [4], wherein at least one of the first member and the second member is a semiconductor element. [6] The method for producing a bonded body according to any one of [1] to [5], wherein the ratio of the total area of the droplets to the surface of the metal particle-containing layer is 3 to 50%.
[0011] [7] A metal paste comprising metal particles and a liquid dispersion medium that is liquid at 25°C, the liquid dispersion medium containing a first compound and a second compound having a lower boiling point and a smaller SP value than the first compound, and the metal paste containing a third compound having a smaller SP value than the second compound. [8] A metal paste comprising metal particles and a liquid dispersion medium that is liquid at 25°C, wherein the liquid dispersion medium contains a polyether alcohol compound and an alcohol compound having a boiling point lower than that of the polyether alcohol compound and having a hydrocarbon group with 8 or more carbon atoms, and the metal paste contains a fatty acid having 10 or more carbon atoms. [9] The metal paste according to [7] or [8], wherein the metal particles contain sub-micro copper particles, spherical micro copper particles, and flake-shaped micro copper particles.
[10] A method for producing a metal paste, comprising the steps of: preparing at least a first compound that is liquid at 25°C; a second compound that is liquid at 25°C and has a lower boiling point and a smaller SP value than the first compound; a third compound that is liquid at 25°C and has a smaller SP value than the second compound; and metal particles; and preparing a dispersion liquid containing the first compound, the second compound, the third compound, and the metal particles.
[11] A method for producing a metal paste, comprising the steps of: preparing at least a polyether alcohol-based compound that is liquid at 25°C; an alcohol-based compound that is liquid at 25°C and has a boiling point lower than that of the polyether alcohol-based compound and has a hydrocarbon group having 8 or more carbon atoms; a fatty acid having 10 or more carbon atoms; and metal particles; and preparing a dispersion liquid containing the polyether alcohol-based compound, the alcohol-based compound, the fatty acid, and the metal particles.
[12] The method for producing a metal paste according to
[10] or
[11] , wherein sub-micro copper particles, spherical micro copper particles, and flake-shaped micro copper particles are prepared as the metal particles.
[13] A metal-pasted member comprising: a member; and a coating film of the metal paste according to any one of [7] to [9] provided on the member.
[0012] According to the method for producing a bonded body described in [1] above, by generating droplets on the surface of the metal particle-containing layer, it is possible to obtain tackiness to the second component and to prevent the second component from falling off during transportation.
[0013] According to the manufacturing method of the bonded body described in [2] above, since the metal paste contains the first compound, the second compound and the third compound defined above, a coating film of the metal paste is well formed, while the second compound is preferentially removed in the second step, so that the affinity between the first compound and the third compound, which are a combination having far SP values, decreases, and when cooled to room temperature (e.g., 25°C or lower), the first compound, which is a liquid dispersion medium, can be separated as droplets on the surface of the metal particle-containing layer. Furthermore, according to the method for manufacturing a bonded body described in [3] above, the metal paste contains the polyether alcohol-based compound defined above, an alcohol-based compound having a hydrocarbon group with 8 or more carbon atoms, and a fatty acid having 10 or more carbon atoms, and thereby a coating film of the metal paste is well formed, while the alcohol-based compound having a hydrocarbon group with 8 or more carbon atoms is preferentially removed in the second step, thereby decreasing the affinity between the polyether alcohol-based compound, which has a combination of high hydrophilicity and low hydrophilicity, and the fatty acid having 10 or more carbon atoms, and when cooled to room temperature (e.g., 25°C or less), the polyether alcohol-based compound, which is a liquid dispersion medium, can be separated as droplets on the surface of the metal particle-containing layer. Effect of the Invention
[0014] According to the present invention, it is possible to provide a method for manufacturing a bonded body that can sufficiently suppress the falling off of components in the production of a bonded body using a metal paste, as well as a metal paste that can be used in such a method and a method for manufacturing the same. [Brief description of the drawings]
[0015] [Figure 1] (a) is a surface image of a metal particle-containing layer on which droplets have been generated, and (b) is a binarized image of the surface image (a). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS The present invention will be described in detail below with reference to the following embodiments.
[0017] <Method of manufacturing the bonded body> The method for producing a joint body of the present embodiment includes a first step of applying a metal paste containing metal particles and a liquid dispersion medium that is liquid at 25°C onto a first component to form a coating film of the metal paste, a second step of removing a portion of the liquid dispersion medium from the coating film to form a metal particle-containing layer, a third step of placing a second component on the metal particle-containing layer to obtain a laminate, and a fourth step of sintering the metal particle-containing layer of the laminate, where droplets are generated on the surface of the metal particle-containing layer in the second step.
[0018] According to the method for producing a bonded body of the present embodiment, a bonded body including a first member, a second member, and a sintered body of a metal particle-containing layer bonding these members can be produced with good yield.
[0019] Examples of the first member and the second member include semiconductor elements such as IGBTs, diodes, Schottky barrier diodes, MOS-FETs, thyristors, logic, sensors, analog integrated circuits, LEDs, semiconductor lasers, and oscillators, base materials for mounting semiconductor elements such as lead frames, metal plate-attached ceramic substrates (e.g., DBC), and LED packages, power supply members such as copper ribbons, metal blocks, and terminals, heat sinks, and water-cooled plates.
[0020] The first member and the second member may have a metal layer on the joining surface that forms a metal bond with the sintered body of the metal paste. Examples of metals constituting the metal layer include copper, nickel, silver, gold, palladium, platinum, lead, tin, cobalt, etc. These metals may be used alone or in combination of two or more. The metal layer may also be an alloy containing the above metals. In addition to the above metals, examples of metals used in the alloy include zinc, manganese, aluminum, beryllium, titanium, chromium, iron, molybdenum, etc. Examples of members having a metal layer include members having various metal platings, wires, chips having metal platings, heat spreaders, ceramic substrates to which metal plates are attached, lead frames having various metal platings or lead frames made of various metals, copper plates, and copper foils.
[0021] (1st step) The metal paste used in this embodiment may be any paste that contains metal particles and a liquid dispersion medium that is liquid at 25° C. and that can generate droplets on the surface of the metal particle-containing layer in the second step.
[0022] The following metal pastes can be used: (i) A metal paste comprising metal particles and a liquid dispersion medium that is liquid at 25°C, wherein the liquid dispersion medium contains a first compound and a second compound having a lower boiling point and a smaller SP value than the first compound, and the metal paste contains a third compound having a smaller SP value than the second compound (hereinafter sometimes referred to as "metal paste 1"). (ii) A metal paste comprising metal particles and a liquid dispersion medium that is liquid at 25°C, wherein the liquid dispersion medium contains a polyether alcohol compound and an alcohol compound having a boiling point lower than that of the polyether alcohol compound and having a hydrocarbon group with 8 or more carbon atoms, and the metal paste contains a fatty acid with 10 or more carbon atoms (hereinafter sometimes referred to as "metal paste 2").
[0023] In this specification, the "SP value" refers to a solubility parameter, and is a value defined by the Hildebrand method (see Non-Patent Document 2 mentioned above) based on the regular solution theory.
[0024] Examples of metal particles include copper particles, silver particles, gold particles, platinum group particles (platinum, palladium, rhodium, iridium), magnetic particles (iron, cobalt, nickel), light metal particles (aluminum, beryllium, magnesium, titanium, alkali metals, alkaline earth metals), low melting point particles (tin, indium, lead, germanium), other general transition metal particles, semimetal particles, and alloy particles combining two or more of these. The metal paste can contain copper particles as metal particles. In this case, the metal oxide film on the particle surface is easily reduced by the reducing solvent used in the paste, making it possible to sinter even under mild conditions of low temperature (300°C or less) and low pressure (10 MPa or less).
[0025] The copper particles include submicro copper particles and micro copper particles. The copper particles refer to particles containing copper as a main component, for example, particles having a copper content of 80% by mass or more. The copper content of the copper particles may be 85% by mass or more, 90% by mass or more, 95% by mass or more, 99% by mass or more, or 100% by mass.
[0026] The sub-micro copper particles may be copper particles having sinterability in a temperature range of 200°C to 380°C. Examples of the sub-micro copper particles include copper particles having a particle size of 0.05 μm to 0.8 μm. For example, copper particles having a volume average particle size of 0.05 μm to 0.8 μm can be used. If the volume average particle size of the sub-micro copper particles is 0.05 μm or more, effects such as reduction in the synthesis cost of the sub-micro copper particles, good dispersibility, and reduction in the amount of organic protective agent used can be easily obtained. If the volume average particle size of the sub-micro copper particles is 0.8 μm or less, the effect of excellent sinterability of the sub-micro copper particles can be easily obtained. From the viewpoint of further achieving the above effect, the volume average particle size of the sub-micro copper particles may be 0.6 μm or less, 0.5 μm or less, or 0.4 μm or less. In addition, the volume average particle size of the sub-micro copper particles may be 0.05 μm or more, 0.07 μm or more, or 0.1 μm or more. The volume average particle size of the submicro copper particles may be, for example, 0.05 μm or more and 0.5 μm or less, 0.07 μm or more and 0.8 μm or less, 0.08 μm or more and 0.8 μm or less, 0.08 μm or more and 0.6 μm or less, 0.1 μm or more and 0.5 μm or less, or 0.2 μm or more and 0.45 μm or less.
[0027] In this specification, the volume average particle size means a 50% volume average particle size. When determining the volume average particle size of metal particles, the metal particles as raw material or dried copper particles obtained by removing volatile components from a metal paste are dispersed in a dispersion medium using a dispersant, and the resulting dispersion medium is measured using a light scattering particle size distribution measuring device (for example, Shimadzu nanoparticle size distribution measuring device (SALD-7500nano, manufactured by Shimadzu Corporation)). When using a light scattering particle size distribution measuring device, hexane, toluene, α-terpineol, 4-methyl-1,3-dioxolan-2-one, water, etc. can be used as the dispersion medium.
[0028] The content of the submicro copper particles may be 20% by mass or more, 30% by mass or more, 35% by mass or more, 40% by mass or more, 90% by mass or less, 85% by mass or less, 80% by mass or less, 20% by mass or more and 90% by mass or less, 30% by mass or more and 90% by mass or less, 35% by mass or more and 85% by mass or less, 40% by mass or more and 80% by mass or less, or 60% by mass or more and 80% by mass or less, based on the total mass of the metal particles. If the content of the submicro copper particles is within the above range, it is easy to ensure the bonding strength of the bonded body, and when the bonded member is a semiconductor element, the semiconductor device tends to exhibit good die shear strength and connection reliability.
[0029] The content of the submicro copper particles may be 20% by mass or more and 90% by mass or less based on the total mass of the copper particles. If the content of the submicro copper particles is 20% by mass or more, when used in combination with micro copper particles such as flake-shaped micro copper particles, the spaces between the copper particles can be sufficiently filled, making it easier to ensure the bonding strength of the bonded body, and when the bonded members are semiconductor elements, the semiconductor device tends to exhibit good die shear strength and connection reliability. If the content of the submicro copper particles is 90% by mass or less, the volume shrinkage in the in-plane direction (XY direction) of the sintered layer when sintered without pressure or under pressure can be sufficiently suppressed, making it easier to ensure the bonding strength of the bonded body, and when the bonded members are semiconductor elements, the semiconductor device tends to exhibit good die shear strength and connection reliability. From the viewpoint of further achieving the above-mentioned effect, the content of the submicro copper particles may be, based on the total mass of the copper particles, 30 mass% or more, 35 mass% or more, 40 mass% or more, 85 mass% or less, 83 mass% or less, 80 mass% or less, 30 mass% or more and 85 mass% or less, 35 mass% or more and 85 mass% or less, 40 mass% or more and 80 mass% or less, or 60 mass% or more and 80 mass% or less.
[0030] The shape of the submicro copper particles is not particularly limited. Examples of the shape of the submicro copper particles include spherical, clumpy, needle-like, flake-like, approximately spherical, and aggregates thereof. From the viewpoint of dispersibility and packing, the shape of the submicro copper particles may be spherical, approximately spherical, or flake-like, and from the viewpoint of combustibility, dispersibility, mixability with flake-like microparticles, etc., it may be spherical or approximately spherical. In this specification, the term "flake-like" includes flat shapes such as plate-like and scale-like.
[0031] From the viewpoints of dispersibility, packing property, and mixability with flake-shaped microparticles, the sub-micro copper particles may have an aspect ratio of 5 or less, 4 or less, or 3 or less. In this specification, the "aspect ratio" refers to the long side (major axis) / thickness of a particle. The long side (major axis) and thickness of a particle can be measured, for example, from an SEM image of the particle.
[0032] The sub-micro copper particles may be treated with a surface treatment agent, such as an organic acid having 2 to 18 carbon atoms.Examples of organic acids having 2 to 18 carbon atoms include acetic acid, propanoic acid, butanoic acid, pentanoic acid, hexanoic acid, heptanoic acid, caprylic acid, methylheptanoic acid, ethylhexanoic acid, propylpentanoic acid, pelargonic acid, methyloctanoic acid, ethylheptanoic acid, propylhexanoic acid, capric acid, methylnonanoic acid, ethyloctanoic acid, propylheptanoic acid, butylhexanoic acid, undecanoic acid, methyldecanoic acid, ethylnonanoic acid, propyloctanoic acid, butylheptanoic acid, lauric acid, methylundecanoic acid, ethyldecanoic acid, propylnon ... , butyl octanoic acid, pentyl heptanoic acid, tridecanoic acid, methyl dodecanoic acid, ethyl undecanoic acid, propyl decanoic acid, butyl nonanoic acid, pentyl octanoic acid, myristic acid, methyl tridecanoic acid, ethyl dodecanoic acid, propyl undecanoic acid, butyl decanoic acid, pentyl nonanoic acid, hexyl octanoic acid, pentadecanoic acid, methyl tetradecanoic acid, ethyl tridecanoic acid, propyl dodecanoic acid, butyl undecanoic acid, pentyl decanoic acid, hexyl nonanoic acid, palmitic acid, methyl pentadecanoic acid, ethyl tetradecanoic acid, proline saturated fatty acids such as propyltridecanoic acid, butyldodecanoic acid, pentylundecanoic acid, hexyldecanoic acid, heptylnonanoic acid, heptadecanoic acid, octadecanoic acid, methylcyclohexanecarboxylic acid, ethylcyclohexanecarboxylic acid, propylcyclohexanecarboxylic acid, butylcyclohexanecarboxylic acid, pentylcyclohexanecarboxylic acid, hexylcyclohexanecarboxylic acid, heptylcyclohexanecarboxylic acid, octylcyclohexanecarboxylic acid, and nonylcyclohexanecarboxylic acid; octenoic acid, nonenoic acid, methylnonanoic acid, unsaturated fatty acids such as decenoic acid, decenoic acid, undecenoic acid, dodecenoic acid, tridecenoic acid, tetradecenoic acid, myristoleic acid, pentadecenoic acid, hexadecenoic acid, palmitoleic acid, sapienic acid, oleic acid, vaccenic acid, linoleic acid, linolenic acid, and linolenic acid; aromatic carboxylic acids such as terephthalic acid, pyromellitic acid, o-phenoxybenzoic acid, methylbenzoic acid, ethylbenzoic acid, propylbenzoic acid, butylbenzoic acid, pentylbenzoic acid, hexylbenzoic acid, heptylbenzoic acid, octylbenzoic acid, and nonylbenzoic acid. The organic acid may be used alone or in combination of two or more.By combining such an organic acid with the sub-micron copper particles, it tends to be possible to achieve both the dispersibility of the sub-micron copper particles and the desorption property of the organic acid during sintering.
[0033] The amount of the surface treatment agent to be treated may be an amount that adheres to the surface of the sub-micro copper particles in one to three molecular layers. This amount depends on the number of molecular layers (n) adhered to the surface of the sub-micro copper particles, the specific surface area (A p ) (unit: m 2 / g) and the molecular weight of the surface treatment agent (M s ) (unit: g / mol) and the minimum coverage area of the surface treatment agent (S S ) (unit: m 2 / piece) and Avogadro's number (N A )(6.02×10 23 Specifically, the amount of surface treatment agent can be calculated by the amount of surface treatment agent (mass%) = {(n·A p M s ) / (S S N A +n·A p M s )}×100%.
[0034] The specific surface area of the submicro copper particles can be calculated by measuring the dried submicro copper particles using the BET specific surface area measurement method. The minimum coverage area of the surface treatment agent is 2.05 × 10 -19 m 2 The carbon content of the surface treatment agent is 1 / molecule. In the case of other surface treatment agents, it can be measured, for example, by calculation from a molecular model or by the method described in "Chemistry and Education" (Katsuhiro Ueda, Sumio Inafuku, Iwao Mori, 40(2), 1992, p114-117). An example of a method for quantifying the surface treatment agent is shown below. The surface treatment agent can be identified by a thermal desorption gas-gas chromatograph mass spectrometer of the dried powder obtained by removing the dispersing medium from the metal paste, and the carbon number and molecular weight of the surface treatment agent can be determined. The carbon content of the surface treatment agent can be analyzed by carbon content analysis. Examples of carbon content analysis methods include high-frequency induction heating furnace combustion / infrared absorption method. The amount of the surface treatment agent can be calculated from the carbon number, molecular weight and carbon content of the identified surface treatment agent using the above formula.
[0035] The amount of the surface treatment agent may be, based on the mass of the sub-micro copper particles having the surface treatment agent, 0.07% by mass or more, 0.1% by mass or more, 0.2% by mass or more, 2.1% by mass or less, 1.6% by mass or less, 1.1% by mass or less, 0.07% by mass or more and 2.1% by mass or less, 0.10% by mass or more and 1.6% by mass or less, or 0.2% by mass or more and 1.1% by mass or less.
[0036] Submicro copper particles can be commercially available. Commercially available submicro particles include, for example, CH-0200 (manufactured by Mitsui Mining & Smelting Co., Ltd., volume average particle diameter 0.36 μm), CH-0200A-L1 (manufactured by Mitsui Mining & Smelting Co., Ltd., volume average particle diameter 0.21 μm), HT-14 (manufactured by Mitsui Mining & Smelting Co., Ltd., volume average particle diameter 0.41 μm), CT-500 (manufactured by Mitsui Mining & Smelting Co., Ltd., volume average particle diameter 0.72 μm), and Tn-Cu100 (manufactured by Taiyo Nippon Sanso Co., Ltd., volume average particle diameter 0.12 μm).
[0037] As the micro copper particles, copper particles having a particle size of 2 μm to 50 μm can be used, for example, copper particles having a volume average particle size of 2 μm to 50 μm. If the volume average particle size of the micro copper particles is within the above range, the volume shrinkage in the in-plane direction (XY direction) of the sintered layer when sintered without pressure or under pressure, the generation of voids, etc. can be sufficiently reduced, the bonding strength of the bonded body can be easily ensured, and when the bonded member is a semiconductor element, the semiconductor device tends to exhibit good die shear strength and connection reliability. From the viewpoint of further achieving the above effect, the volume average particle size of the micro copper particles may be 2 μm or more, 3 μm or more, 20 μm or less, 15 μm or less, 10 μm or less, 2 μm to 20 μm, 2 μm to 10 μm, 3 μm to 20 μm, or 3 μm to 10 μm.
[0038] The shape of the micro copper particles is preferably flake-shaped. By using flake-shaped micro copper particles, the micro copper particles in the metal particle-containing layer are oriented approximately parallel to the bonding surface, so that the volume shrinkage when the metal particle-containing layer is sintered can be suppressed, and the bonding strength of the bonded body can be easily ensured. When the members to be bonded are semiconductor elements, the semiconductor device tends to exhibit good die shear strength and connection reliability. From the viewpoint of further achieving the above effect, the flake-shaped micro copper particles may have an aspect ratio of more than 2, 4 or more, 6 or more, 10 or more, or 50 or more.
[0039] The content of the micro copper particles may be 10% by mass or more and 90% by mass or less, 15% by mass or more and 65% by mass or less, or 20% by mass or more and 60% by mass or less, based on the total mass of the copper particles. If the content of the micro copper particles is within the above range, it is easy to ensure the bonding strength of the bonded body, and when the bonded members are semiconductor elements, the semiconductor device tends to exhibit good die shear strength and connection reliability.
[0040] In the micro copper particles, the presence or absence of treatment with a surface treatment agent is not particularly limited, but from the viewpoint of dispersion stability and oxidation resistance, the micro copper particles may be treated with a surface treatment agent. The surface treatment agent may be one that is removed during bonding. Examples of such surface treatment agents include aliphatic carboxylic acids such as dodecanoic acid, palmitic acid, heptadecanoic acid, stearic acid, arachidic acid, linoleic acid, linoleic acid, and oleic acid; aromatic carboxylic acids such as terephthalic acid, pyromellitic acid, and o-phenoxybenzoic acid; aliphatic alcohols such as cetyl alcohol, stearyl alcohol, isobornylcyclohexanol, and tetraethylene glycol; aromatic alcohols such as p-phenylphenol; alkylamines such as octylamine, dodecylamine, and stearylamine; aliphatic nitriles such as stearonitrile and decanenitrile; silane coupling agents such as alkylalkoxysilanes; and polymer treatment agents such as polyethylene glycol, polyvinyl alcohol, polyvinylpyrrolidone, and silicone oligomers. The surface treatment agent may be used alone or in combination of two or more.
[0041] The amount of the surface treatment agent may be more than one molecular layer on the particle surface. The amount of the surface treatment agent varies depending on the specific surface area of the micro copper particles, the molecular weight of the surface treatment agent, and the minimum coverage area of the surface treatment agent. The amount of the surface treatment agent may be 0.001% by mass or more and 2.0% by mass or less, 0.4% by mass or more and 2.0% by mass or less, or 0.5% by mass or more and 1.7% by mass or less, based on the mass of the micro copper particles having the surface treatment agent. The specific surface area of the micro copper particles, the molecular weight of the surface treatment agent, and the minimum coverage area of the surface treatment agent can be calculated by the same method as in the case of the sub-micro copper particles described above.
[0042] The micro copper particles may be commercially available. Commercially available spherical microparticles include, for example, Cu-HWQ1.5 μm (manufactured by Fukuda Metal Foil & Powder Co., Ltd., volume average particle size 1.5 μm), Cu-HWQ3 μm (manufactured by Fukuda Metal Foil & Powder Co., Ltd., volume average particle size 3 μm), Cu-HWQ5 μm (manufactured by Fukuda Metal Foil & Powder Co., Ltd., volume average particle size 5 μm), Cu-HWQ10 μm (manufactured by Fukuda Metal Foil & Powder Co., Ltd., volume average particle size 10 μm), 1110 (manufactured by Mitsui Mining & Smelting Co., Ltd., volume average particle size 3.6 μm), 1100Y (manufactured by Mitsui Mining & Smelting Co., Ltd., volume average particle size 1.1 μm), 1200Y (manufactured by Mitsui Mining & Smelting Co., Ltd., volume average particle size 2.1 μm), 1300Y (manufactured by Mitsui Mining & Smelting Co., Ltd., volume average particle size 3.5 μm), MA-C02K (manufactured by Mitsui Mining & Smelting Co., Ltd., volume average particle size 2.2 μm), 1300Y (manufactured by Mitsui Mining & Smelting Co., Ltd., volume average particle size 3.5 μm), and 1110 (manufactured by Mitsui Mining & Smelting Co., Ltd., volume average particle size 3.6 μm). average particle diameter 1.8 μm), MA-C025K (manufactured by Mitsui Mining & Smelting Co., Ltd., volume average particle diameter 2.4 μm), MA-C03K (manufactured by Mitsui Mining & Smelting Co., Ltd., volume average particle diameter 3.4 μm), MA-C05K (manufactured by Mitsui Mining & Smelting Co., Ltd., volume average particle diameter 5.8 μm), MA-C05K-2 (manufactured by Mitsui Mining & Smelting Co., Ltd., volume average particle diameter 5.1 μm), MA-C08K-2 (manufactured by Mitsui Mining & Smelting Co., Ltd., volume average particle diameter 8.2 μm), MA-CKU (manufactured by Mitsui Mining & Smelting Co., Ltd., volume average particle diameter 11.1 μm), MA-C04J (manufactured by Mitsui Mining & Smelting Co., Ltd., volume average particle diameter 4.3 μm), MA-C08J (manufactured by Mitsui Mining & Smelting Co., Ltd., volume average particle diameter 8.2 μm), and MA-CJU (manufactured by Mitsui Mining & Smelting Co., Ltd., volume average particle diameter 17.7 μm).
[0043] Examples of commercially available flake-shaped microparticles include 1100YP (manufactured by Mitsui Mining & Smelting Co., Ltd., volume average particle size 1.4 μm), 1200YP (manufactured by Mitsui Mining & Smelting Co., Ltd., volume average particle size 3.1 μm), MA-C08JF (manufactured by Mitsui Mining & Smelting Co., Ltd., volume average particle size 11.9 μm), MA-C03KP (manufactured by Mitsui Mining & Smelting Co., Ltd., volume average particle size 3.5 μm), MA-C05KP (manufactured by Mitsui Mining & Smelting Co., Ltd., volume average particle size 5.8 μm), MA-C025KFD (manufactured by Mitsui Mining & Smelting Co., Ltd., volume average particle size 4.7 μm), MA-C05KFD (manufactured by Mitsui Mining & Smelting Co., Ltd., volume average particle size 4.7 μm), and MA-C05KFD (manufactured by Mitsui Mining & Smelting Co., Ltd.). Examples of such powders include 1110F (manufactured by Mitsui Mining & Smelting Co., Ltd., volume average particle size 7.3 μm), 1110F (manufactured by Mitsui Mining & Smelting Co., Ltd., volume average particle size 3.8 μm), 3L3N (manufactured by Fukuda Metal Foil & Powder Co., Ltd., volume average particle size 6 μm), 2L3N (manufactured by Fukuda Metal Foil & Powder Co., Ltd., volume average particle size 9.9 μm), 4L3N (manufactured by Fukuda Metal Foil & Powder Co., Ltd., volume average particle size 3 μm), C3 (manufactured by Fukuda Metal Foil & Powder Co., Ltd., volume average particle size 37 μm), Cu-HWF-6 (manufactured by Fukuda Metal Foil & Powder Co., Ltd., volume average particle size 6 μm), and ST-Cu-325 (manufactured by Yamaishi Metals Co., Ltd., volume average particle size 30 μm).
[0044] The third compound in the metal paste 1 and the fatty acid having 10 or more carbon atoms in the metal paste 2 may be blended separately from the surface treatment agent for the sub-micro copper particles and the surface treatment agent for the micro copper particles. In this case, droplets are easily generated in the second step.
[0045] The metal paste may contain sub-micro copper particles and micro copper particles as metal particles. In this case, the volume shrinkage and sintering shrinkage caused by drying of the dispersion medium can be suppressed, and it becomes easy to prevent peeling between the joining surface of the member and the sintered body of the metal particle-containing layer.
[0046] From the above viewpoint, the metal paste may comprise sub-micro copper particles having a volume average particle size of 0.05 μm or more and 0.8 μm or less, and spherical micro copper particles having a volume average particle size of 2 μm or more and 50 μm or less, and the sum of the content of the sub-micro copper particles and the content of the micro copper particles may be 80 mass % or more or 90 mass % or more based on the total mass of the metal particles, and the content of the sub-micro copper particles may be 30 mass % or more and 90 mass % or less based on the sum of the mass of the sub-micro copper particles and the mass of the micro copper particles.
[0047] The metal paste may contain sub-micro copper particles, flaky micro copper particles, and spherical micro copper particles from the viewpoints of low-temperature sintering properties, suppression of volumetric shrinkage in the XY directions (directions parallel to the joining surface), and improving the filling of the metal particles in the metal particle-containing layer.
[0048] From the above viewpoint, the metal paste includes sub-micro copper particles having a volume average particle size of 0.05 μm to 0.8 μm, spherical micro copper particles having a volume average particle size of 2 μm to 50 μm and an aspect ratio of 2 or less, and flaky micro copper particles having an aspect ratio of more than 2, and the total content of the sub-micro copper particles, the spherical micro copper particles, and the flaky micro copper particles is 80 mass % or more or 90 mass % or more based on the total mass of the metal particles, and the content of the sub-micro copper particles, the spherical micro copper particles, and the flaky micro copper particles may be 20 mass % to 80 mass %, 5 mass % to 50 mass %, and 5 mass % to 50 mass %, respectively, based on the total mass thereof, or may be 60 mass % to 80 mass %, 10 mass % to 20 mass %, and 10 mass % to 20 mass %.
[0049] The metal paste may contain metal particles (other metal particles) containing a metal element other than copper as the metal particles. The other metal particles may contain, for example, zinc, gold, palladium, silver, nickel, platinum, brass, manganese, tin, antimony, indium, aluminum, vanadium, etc. The other metal particles may have a volume average particle size of 0.01 μm or more and 10 μm or less, 0.01 μm or more and 5 μm or less, or 0.05 μm or more and 3 μm or less.
[0050] When the metal paste contains other metal particles, a sintered body in which multiple metals are dissolved or dispersed can be obtained, improving mechanical properties such as yield stress and fatigue strength of the sintered body, and improving connection reliability. In addition, by adding multiple metal particles, the sintered body of the metal particle-containing layer can have sufficient bonding strength to a predetermined adherend. When the member to be bonded is a semiconductor element, the die shear strength and connection reliability of the semiconductor device can be easily improved.
[0051] When the metal paste contains other metal particles, the content of the other metal particles may be less than 5 mass% or may be 3 mass% or less based on the total mass of the metal particles from the viewpoint of obtaining sufficient bonding properties. The other metal particles may not be contained. The shape of the other metal particles is not particularly limited.
[0052] The content of inorganic particles other than metal particles in the metal paste may be 30 mass % or less, 20 mass % or less, or 0 mass % based on the total amount of the bonding metal paste.
[0053] Examples of liquid dispersion media include monohydric and polyhydric alcohols such as pentanol, hexanol, heptanol, octanol, decanol, dihydroterpineol, terpineol, isobornylcyclohexanol (MTPH), 1,5-pentanediol, ethylene glycol, diethylene glycol, propylene glycol, butylene glycol, triethylene glycol, tetraethylene glycol, α-terpineol (α-terpineol), dihydroterpineol (dihydroterpineol), and geraniol; ethylene glycol butyl ether, ethylene glycol phenyl ether, diethylene glycol methyl ether, diethylene glycol ethyl ether, diethylene glycol butyl ether, diethylene glycol isobutyl ether, diethylene glycol hexyl ether, triethylene glycol methyl ether, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol dibutyl ether, diethylene glycol butyl methyl ether, diethylene glycol isopropyl methyl ether, and triethylene glycol di Ethers such as methyl ether, triethylene glycol butyl methyl ether, propylene glycol propyl ether, dipropylene glycol methyl ether, dipropylene glycol ethyl ether, dipropylene glycol propyl ether, dipropylene glycol butyl ether, dipropylene glycol dimethyl ether, tripropylene glycol methyl ether, and tripropylene glycol dimethyl ether; esters such as ethylene glycol ethyl ether acetate, ethylene glycol butyl ether acetate, diethylene glycol ethyl ether acetate, diethylene glycol butyl ether acetate, dipropylene glycol methyl ether acetate (DPMA), ethyl lactate, butyl lactate, γ-butyrolactone, and propylene carbonate; acid amides such as N-methyl-2-pyrrolidone, N,N-dimethylacetamide, and N,N-dimethylformamide; aliphatic hydrocarbons such as cyclohexanone, octane, nonane, decane, and undecane; aromatic hydrocarbons such as benzene, toluene, xylene, and 1-methylnaphthalene; mercaptans having an alkyl group having 1 to 18 carbon atoms;Examples of mercaptans having a cycloalkyl group having 5 to 7 carbon atoms include mercaptans having an alkyl group having 1 to 18 carbon atoms include ethyl mercaptan, n-propyl mercaptan, i-propyl mercaptan, n-butyl mercaptan, i-butyl mercaptan, t-butyl mercaptan, pentyl mercaptan, hexyl mercaptan, and dodecyl mercaptan. Examples of mercaptans having a cycloalkyl group having 5 to 7 carbon atoms include cyclopentyl mercaptan, cyclohexyl mercaptan, and cycloheptyl mercaptan.
[0054] The content of the liquid dispersion medium in the metal paste may be 2% by mass or more, or 5% by mass or more, or 50% by mass or less, 30% by mass or less, or 20% by mass or less, based on the total mass of the metal paste. For example, the content of the liquid dispersion medium may be 2 to 50% by mass, 5 to 30% by mass, or 5 to 20% by mass, based on the total mass of the metal paste. Furthermore, the content of the metal paste may be 5 to 50 parts by mass, 5 to 40 parts by mass, or 7 to 35 parts by mass, based on the total mass of the metal particles contained in the metal paste being 100 parts by mass. If the content of the liquid dispersion medium is within the above range, the viscosity of the metal paste can be adjusted to a more appropriate level, and droplets can be easily generated on the surface of the metal particle-containing layer.
[0055] In this embodiment, two or more liquid dispersion media can be used in combination.
[0056] The metal paste 1 contains, as a liquid dispersion medium, a first compound, a second compound having a lower boiling point and a smaller SP value than the first compound, and a third compound having a smaller SP value than the second compound.
[0057] The first compound may have a boiling point of 260 to 330° C., 250 to 320° C., or 240 to 300° C. The second compound may have a boiling point of 230° C. or lower, 220° C. or lower, or 210° C. or lower The third compound may have a boiling point of 260 to 330° C., 250 to 320° C., or 240 to 300° C.
[0058] The difference between the boiling point of the first compound and the boiling point of the second compound may be 30 to 120°C, or 70 to 100°C.
[0059] The first compound may have an SP value of 23 or more, 24 to 32, or 25 to 30. The second compound may have an SP value of 19 to 20, 19.1 to 19.9, or 19.2 to 19.8. The third compound may have an SP value of less than 19, 15 to 18.9, or 16 to 18.5.
[0060] The difference between the SP value of the first compound and the SP value of the second compound may be 4 to 13, or 4.5 to 10. The difference between the SP value of the second compound and the SP value of the third compound may be 0.1 to 5, or 0.5 to 3.
[0061] From the viewpoint of resistance to volatility during the drying process, the first compound has a vapor pressure of 1×10 -6 ~1×10 -3 mmHg, 1 x 10 -5 ~1×10 -4 It may be in mmHg.
[0062] The first compound may function as a reducing agent, and may be a polyether alcohol-based compound from the viewpoints of ease of droplet generation in the chip mounting step and good desorption properties in the sintering step.
[0063] As the first compound, for example, triethylene glycol, tetraethylene glycol, 1,5-pentanediol, diethylene glycol, glycerin, diglycerin, and the like can be used.
[0064] From the viewpoint of suppressing the generation of voids in the sintering step, the content of the first compound may be 5 to 35 mass %, 10 to 30 mass %, or 15 to 25 mass % based on the total mass of the liquid dispersion medium.
[0065] From the viewpoint of volatility resistance, the second compound has a vapor pressure of 1×10 -4 ~1×10 -2 mmHg, 1 x 10 -3 ~1×10 -2 In these cases, the paste tends to maintain stable applicability.
[0066] From the viewpoint of good dispersibility of the metal particles, the second compound may be an alcohol-based compound having a hydrocarbon group having 8 or more carbon atoms.
[0067] As the second compound, for example, α-terpineol, dihydroterpineol, geraniol, 1-methylnaphthalene, 1-decanol, limonene, terpinyl methyl ether, dihydroterpinyl methyl ether, and the like can be used.
[0068] From the viewpoint of good coatability of the paste, the content of the second compound may be 25 to 90 mass %, 30 to 80 mass %, or 35 to 70 mass % based on the total mass of the liquid dispersion medium.
[0069] The third compound may have a functional group (e.g., a carbonyl group, a carboxyl group, an amino group, a thiol group, etc.) capable of coordinatively bonding to the surface of a metal particle (e.g., a copper particle) and may have a low polarity structure (e.g., a hydrocarbon group, a cyclo structure, an aromatic ring such as a benzene ring, etc.). From the viewpoint of the ease of generating droplets in the chip mounting step, the third compound may be a fatty acid having 10 or more carbon atoms, or a fatty acid having 10 to 18 carbon atoms.
[0070] The third compound has a vapor pressure of 1×10 at 25°C from the viewpoint of resistance to volatility during the drying process. -6~1×10 -3 mmHg, 1 x 10 -5 ~1×10 -4 It may be in mmHg.
[0071] As the third compound, for example, lauric acid, stearic acid, dodecylamine, 1-hexadecene, dodecyl acetate, decanoic acid, oleic acid, decylamine, and the like can be used.
[0072] The content of the third compound may be 5 to 100 parts by mass, 10 to 80 parts by mass, or 20 to 60 parts by mass relative to 100 parts by mass of the first compound from the viewpoint of the ease of droplet generation in the chip mounting process. Also, the content of the third compound may be 0.1 to 10 parts by mass, 0.5 to 5 parts by mass, or 1 to 3 parts by mass relative to 100 parts by mass of the metal particles from the viewpoint of suppressing the generation of voids in the sintering process. The content of the third compound may not include the surface treatment agent of the metal particles.
[0073] Metal paste 2 contains, as a liquid dispersion medium, a polyether alcohol compound and an alcohol compound having a lower boiling point than the polyether alcohol compound and a hydrocarbon group having 8 or more carbon atoms. Metal paste 3 also contains a fatty acid having 10 or more carbon atoms.
[0074] The boiling point and vapor pressure at 25° C. of the polyether alcohol compound may be the same as those of the first compound described above.
[0075] Examples of the polyether alcohol compounds include triethylene glycol, tetraethylene glycol, pentaethylene glycol, hexaethylene glycol, and propylene glycol.
[0076] The content of the polyether alcohol compound may be the same as that of the first compound.
[0077] The boiling point and vapor pressure at 25° C. of the alcohol-based compound having a hydrocarbon group having 8 or more carbon atoms may be the same as those for the second compound.
[0078] Examples of alcohol-based compounds having a hydrocarbon group having 8 or more carbon atoms include α-terpineol, dihydroterpineol, geraniol, 1-decanol, 2-phenylethyl alcohol, 2-decanol, and 1-dodecanol.
[0079] The content of the alcohol-based compound having a hydrocarbon group having 8 or more carbon atoms may be the same as the conditions for the second compound described above.
[0080] The difference between the boiling point of the polyether alcohol compound and the boiling point of the alcohol compound having a hydrocarbon group having 8 or more carbon atoms may be 10 to 50°C, or 20 to 40°C.
[0081] The boiling point and vapor pressure at 25° C. of the fatty acid having 10 or more carbon atoms may be the same as those for the third compound described above.
[0082] Examples of fatty acids having 10 or more carbon atoms include lauric acid, stearic acid, decanoic acid, and oleic acid.
[0083] The content of the fatty acid having 10 or more carbon atoms may be 5 to 100 parts by mass, 10 to 80 parts by mass, or 20 to 60 parts by mass relative to 100 parts by mass of the polyether alcohol compound from the viewpoint of the ease of droplet generation in the chip mounting step. Also, the content of the fatty acid having 10 or more carbon atoms may be 0.1 to 10 parts by mass, 0.5 to 5 parts by mass, or 1 to 3 parts by mass relative to 100 parts by mass of the metal particles from the viewpoint of suppressing the generation of voids in the sintering step. Note that the content of the fatty acid having 10 or more carbon atoms may not include the surface treatment agent for the metal particles.
[0084] The metal paste may contain, as additives, wetting improvers such as nonionic surfactants and fluorine-based surfactants; surface tension adjusters; dispersants such as alkylamines and alkylcarboxylic acids; antifoaming agents such as silicone oils; and ion trapping agents such as inorganic ion exchangers. The content of the additives may be appropriately adjusted within a range that does not impair the effects of the present invention. Furthermore, the metal paste may have a total content of nonmetallic inorganic particles (e.g., glass particles, etc.) of 1 mass % or less, or 0.1 mass % or less, based on the total amount of metal particles. Furthermore, the metal paste may not contain nonmetallic inorganic particles.
[0085] The viscosity of the metal paste is not particularly limited, and when it is applied by a method such as printing, it may be adjusted to a viscosity suitable for the application method. The Casson viscosity of the metal paste at 25°C may be 1 Pa·s or more or 100 Pa·s or more, or may be 10 Pa·s or less or 50 Pa·s or less.
[0086] The metal paste can be prepared by mixing the above-mentioned metal particles (e.g., submicro copper particles and micro copper particles), the above-mentioned liquid dispersion medium, a third compound (e.g., a fatty acid having 10 or more carbon atoms), and, if necessary, other metal particles and any additives. After mixing the components, a stirring process may be performed. The maximum particle size of the metal paste dispersion may be adjusted by a classification operation.
[0087] For example, metal paste 1 can be produced by preparing at least a first compound that is liquid at 25°C, a second compound that is liquid at 25°C and has a lower boiling point and a smaller SP value than the first compound, a third compound that has a smaller SP value than the second compound, and metal particles, and preparing a dispersion liquid containing the first compound, the second compound, the third compound, and the metal particles.
[0088] The above method may include a step of preparing a mixed solvent by mixing the first compound, the second compound, and the third compound, and a step of mixing the weighed metal particles (e.g., submicro copper particles and micro copper particles) into the mixed solvent and kneading the mixture. As a kneading method, a general kneading device such as a stirrer, a planetary mill, or a three-roll mill, which will be described later, can be used.
[0089] For example, metal paste 2 can be produced by preparing at least a polyether alcohol-based compound that is liquid at 25°C, an alcohol-based compound that has a lower boiling point than the polyether alcohol-based compound and has a hydrocarbon group with 8 or more carbon atoms and is liquid at 25°C, a fatty acid with 10 or more carbon atoms, and metal particles, and preparing a dispersion liquid containing the polyether alcohol-based compound, the alcohol-based compound, the fatty acid, and metal particles.
[0090] The above method may include a step of preparing a mixed solvent by mixing the above polyether alcohol compound, the above alcohol compound, and the above fatty acid, and a step of mixing the above-mentioned weighed metal particles (e.g., submicro copper particles and micro copper particles) into the mixed solvent and kneading the mixture. The kneading method may be the same as above.
[0091] When sub-micro copper particles and micro copper particles are mixed as metal particles, the metal paste may be prepared by mixing the sub-micro copper particles and the dispersion medium in advance, dispersing the sub-micro copper particles to prepare a dispersion of the sub-micro copper particles, and then mixing the remaining components. By adopting such a procedure, the dispersibility of the sub-micro copper particles is improved, and the mixability with the micro copper particles (e.g., flake micro copper particles, spherical micro copper particles, etc.) is improved, and the performance of the metal paste can be further improved. In addition, aggregates may be removed from the dispersion of the sub-micro copper particles by a classification operation. The sub-micro copper particles may be sub-micro copper particles treated with an organic protective agent.
[0092] The stirring treatment can be carried out using a stirrer, such as an Ishikawa stirrer, a Silverson stirrer, a cavitation stirrer, a rotation-revolution type stirrer, an ultra-thin film high-speed rotary disperser, an ultrasonic disperser, a Raikai machine, a twin-screw kneader, a bead mill, a ball mill, a three-roll mill, a homomixer, a planetary mixer, an ultra-high pressure type disperser, a thin layer shear disperser, or a dispersizer.
[0093] Examples of the dispersion treatment include a thin layer shear disperser, a dispersizer, a bead mill, an ultrasonic homogenizer, a high shear mixer, a narrow gap three-roll mill, a wet type ultra-atomizer, a supersonic jet mill, and an ultra-high pressure homogenizer.
[0094] The classification can be carried out, for example, by filtration, natural sedimentation, or centrifugation. Examples of filters for filtration include water combs, metal meshes, metal filters, and nylon meshes.
[0095] Methods for applying the metal paste onto the first component include inkjet printing, super inkjet printing, screen printing, transfer printing, offset printing, jet printing, dispenser, jet dispenser, needle dispenser, comma coater, slit coater, die coater, gravure coater, slit coat, letterpress printing, intaglio printing, gravure printing, stencil printing, soft lithography, bar coat, applicator, particle deposition method, spray coater, spin coater, dip coater, electrocoating, etc.
[0096] The thickness of the coating film may be 1 μm or more, 5 μm or more, 10 μm or more, or 20 μm or more. Also, the thickness of the coating film may be 3000 μm or less, 1000 μm or less, 500 μm or less, 300 μm or less, 250 μm or less, 200 μm or less, or 150 μm or less.
[0097] (2nd process) In the second step, a part of the liquid dispersion medium is removed from the coating film to form a metal particle-containing layer, and at this time, liquid droplets are generated on the surface of the metal particle-containing layer.
[0098] When the above-mentioned metal paste 1 is used, the coating film is heated and dried or dried under reduced pressure at a predetermined temperature to preferentially remove the second compound, thereby reducing the affinity between the first compound and the third compound, which are a combination with different SP values, and when cooled to room temperature (e.g., 25°C or lower), the first compound, which is a liquid dispersion medium, can be separated as droplets on the surface of the metal particle-containing layer.
[0099] Similarly, when the above-mentioned metal paste 2 is used, the coating film is heated and dried or dried under reduced pressure at a predetermined temperature to preferentially remove the alcohol-based compounds having a hydrocarbon group having 8 or more carbon atoms, thereby reducing the affinity between the polyether alcohol-based compound, which has a combination of high hydrophilicity and low hydrophilicity, and the fatty acid having 10 or more carbon atoms, and when cooled to room temperature (e.g., 25°C or less), the polyether alcohol-based compound, which is a liquid dispersion medium, can be separated as droplets on the surface of the metal particle-containing layer.
[0100] The gas atmosphere during drying by heating or drying under reduced pressure may be air, an oxygen-free atmosphere such as nitrogen or a rare gas, or a reducing atmosphere such as hydrogen or formic acid.
[0101] For drying by heating or drying under reduced pressure, for example, a hot plate, a hot air dryer, a hot air heating furnace, a nitrogen dryer, an infrared dryer, an infrared heating furnace, a far-infrared heating furnace, a microwave heating device, a laser heating device, an electromagnetic heating device, a heater heating device, a steam heating furnace, a hot plate press device, etc. The drying temperature and time may be appropriately adjusted according to the type and amount of the dispersion medium used.
[0102] In this embodiment, from the viewpoint of efficient volatilization of the second compound or the alcohol-based compound in the drying step, the coating film may be heated in the air or in an oxygen-free atmosphere (nitrogen gas, argon gas, vacuum, etc.) at 60 to 100°C for 20 to 120 minutes to form a metal particle-containing layer, and then allowed to cool to 25°C to generate droplets on the surface of the metal particle-containing layer.
[0103] The droplets may have a three-dimensional shape of hemispheres or a shape in which the droplets are connected together. The droplets may have a two-dimensional shape, such as a circle or pseudocircle, when viewed from a direction in which the metal particle-containing layer is viewed in plan, and can be observed with a general optical microscope.
[0104] In the second step, droplets having a diameter of 100 μm to 1 mm may be generated on the surface of the metal particle-containing layer when viewed from a direction in which the metal particle-containing layer is viewed in plan.
[0105] The height of the droplet (the shortest distance between the surface of the metal particle-containing layer and the apex of the droplet) may be 0.1 to 100 μm, 0.5 to 30 μm, or 1 to 10 μm.
[0106] The ratio of the total area of the droplets on the surface of the metal particle-containing layer may be 3 to 50%, 4 to 30%, 5 to 20%, or 5 to 10%, from the viewpoint of ensuring sufficient tack strength.
[0107] The size, area, and above-mentioned ratio of the droplets can be determined by the following method. (i) Using an optical microscope (VR-6000, manufactured by Keyence) capable of three-dimensional shape measurement, a planar observation image in the planar direction of the metal particle-containing layer is obtained (see FIG. 1(a)). (ii) The obtained observation planar image is subjected to image analysis using image analysis software (e.g., ImageJ). In the image analysis, the observation planar image is binarized into black and white, so that the size, area, and the above-mentioned ratio of the droplet can be obtained (see FIG. 1(b)). Note that, if the droplet in the observation planar image has multiple contours, such as multiple circles, the outermost contour can be regarded as the droplet contour, and the size, area, and the above-mentioned ratio of the droplet can be calculated.
[0108] The ratio of the total area of the droplets on the surface of the metal particle-containing layer can be adjusted, for example, by the blending ratio of the metal particles and the remaining solvent (the first compound and the third compound, or the above-mentioned polyether alcohol-based compound and the above-mentioned fatty acid), the blending ratio of the first compound and the third compound or the blending ratio of the above-mentioned polyether alcohol-based compound and the above-mentioned fatty acid, the temperature environment after drying and leaving to stand, etc.
[0109] (3rd step) In the third step, a second member is placed on the metal particle-containing layer on whose surface the droplets are generated to obtain a laminate.
[0110] Methods for placing the second member on the metal particle-containing layer include, for example, using a chip mounter, a flip chip bonder, or a positioning jig made of carbon or ceramics.
[0111] The obtained laminate can be transported to a sintering furnace or the like for carrying out the fourth step. Examples of the transport means include manual transport, an automatic conveyor, a transport machine, an automatic cart, and a robot arm. Since the metal particle-containing layer and the second member are sufficiently temporarily fixed to each other by the tackiness of the droplets, the laminate is unlikely to have a problem in which the second member falls off during the transport.
[0112] (4th step) In the fourth step, the metal particle-containing layer of the laminate can be sintered by heat treatment in an oxygen-free atmosphere. The oxygen-free atmosphere may be an atmosphere that does not contain hydrogen or has a hydrogen concentration of 10% or less. The oxygen-free atmosphere refers to an atmosphere with an oxygen concentration of 1% by volume or less, and the oxygen concentration may be 0.1% by volume or less, 0.01% by volume or less, or 0.001% by volume or less.
[0113] For the heat treatment, a heating device having a pressure bonding mechanism can be used, for example, a hot plate, a hot air dryer, a hot air heating furnace, a nitrogen dryer, an infrared dryer, an infrared heating furnace, a far-infrared heating furnace, a microwave heating device, a laser heating device, an electromagnetic heating device, a heater heating device, a steam heating furnace, etc.
[0114] The hydrogen-free atmosphere may be a non-oxidizing gas such as nitrogen, a rare gas, a heat-resistant organic gas, water vapor, or a mixture of these, or may be under vacuum.
[0115] The gas atmosphere during sintering may be a reducing atmosphere. Examples of the reducing atmosphere include nitrogen containing formic acid gas, rare gas containing formic acid gas, and non-oxidizing gas containing 10% or less hydrogen. The gas atmosphere during sintering may be forming gas (nitrogen containing hydrogen below the lower explosion limit (e.g., 5% or less or 3% or less)) or low molecular weight alcohol (e.g., methanol, ethanol) vapor.
[0116] From the viewpoint of reducing thermal damage to the members to be joined and improving yield, the maximum temperature reached during the heat treatment may be 200°C or higher and 450°C or lower, 230°C or higher and 400°C or lower, 240°C or higher and 350°C or lower, or 250°C or higher and 300°C or lower.
[0117] The time for holding the maximum temperature may be 1 minute or more and 60 minutes or less, or 1 minute or more and less than 40 minutes, or 1 minute or more and less than 30 minutes, from the viewpoint of volatilizing all of the dispersion medium and improving the yield. In particular, when the maximum temperature to be held is 250° C. or more, sintering tends to proceed sufficiently with a holding time of 10 minutes or less.
[0118] Through the fourth step, a bonded body including the first member, the second member, and the sintered body of the metal particle-containing layer bonding them together can be obtained.
[0119] From the viewpoint of sufficiently bonding the first member and the second member, the die shear strength of the bonded body may be 40 MPa or more, 50 MPa or more, 60 MPa or more, or 30 MPa or more. The die shear strength can be measured using a universal bond tester (4000 series, manufactured by DAGE Co., Ltd.) or the like.
[0120] From the viewpoint of heat dissipation and connection reliability at high temperatures, the thermal conductivity of the sintered body may be 100 W / (m K) or more, 150 W / (m K) or more, or 200 W / (m K) or more. The thermal conductivity can be calculated from the thermal diffusivity, specific heat capacity, and density of the sintered body of the metal paste.
[0121] In the above-mentioned bonded body, at least one of the first member and the second member may be a semiconductor element. Examples of the semiconductor element include a power module including a diode, a rectifier, a thyristor, a MOS gate driver, a power switch, a power MOSFET, an IGBT, a Schottky diode, a fast recovery diode, etc., a transmitter, an amplifier, an LED module, etc. In such a case, the above-mentioned bonded body becomes a semiconductor device. The obtained semiconductor device can have sufficient die shear strength and connection reliability.
[0122] Examples of semiconductor devices include power modules consisting of diodes, rectifiers, thyristors, MOS gate drivers, power switches, power MOSFETs, IGBTs, Schottky diodes, fast recovery diodes, etc., transmitters, amplifiers, high-brightness LED modules, semiconductor laser modules, logic, sensors, etc.
[0123] The present invention can provide a metal paste-attached member comprising a member and a coating film of the above-mentioned metal paste provided on the member. This metal paste-attached member can be obtained by the above-mentioned first step. The metal paste-attached member of this embodiment can be converted into a member with a metal particle-containing layer having tackiness by carrying out the above-mentioned second step at a predetermined timing. EXAMPLES
[0124] The present invention will be described in more detail below with reference to examples, although the present invention is not limited to the following examples.
[0125] The evaluations in each of the examples and comparative examples were carried out by the following methods.
[0126] (1) Area ratio of droplets The area ratio of droplets formed on the surface of the metal particle-containing layer was measured by the following procedure.
[0127] A metal paste was applied onto a copper plate (30 mm × 30 mm × 2 mm thick) by stencil printing using a metal mask with a 10 mm × 10 mm square opening on a 0.1 mm thick stainless steel plate and a metal squeegee. Next, the metal paste coating was heated at 70°C for 1 hour using a hot plate and then allowed to cool to room temperature (25°C) to form a metal particle-containing layer.
[0128] The surface of the metal particle-containing layer was observed under an optical microscope to confirm the presence or absence of droplets. If droplets were present, the area ratio of the droplets was calculated by the following procedure. (i) Using an optical microscope (VR-6000, manufactured by Keyence) capable of three-dimensional shape measurement, a planar observation image of the metal particle-containing layer in the planar direction was obtained. (ii) The obtained observation planar image was subjected to image analysis using ImageJ. In the image analysis, the observation planar image was binarized into black and white to calculate the area ratio of the droplets generated on the surface of the metal particle-containing layer. Note that, when the droplets in the observation planar image had multiple contours such as multiple circles, the outermost contour was regarded as the droplet contour.
[0129] (2) Adhesion strength between the metal particle-containing layer and the silicon chip A silicon chip (area 5 mm × 5 mm, thickness 150 μm, having a copper sputtered layer as the adhesion surface (bonding surface)) was mounted on the metal particle-containing layer formed in the same manner as in (1) using a desktop manual die bonder (T-3000-FC3, manufactured by Dr. TRESKY) under conditions of room temperature of 25°C, load of 2.5 kg, and load application time of 1 second to obtain a laminate.
[0130] For the resulting laminate, the tack strength between the metal particle-containing layer and the silicon chip was measured by the following procedure. The silicon chip of the obtained laminate was pressed horizontally at a measurement speed of 100 μm / s and a measurement height of 100 μm using a universal bond tester (STELLAR4000, manufactured by Nordson Corp.) equipped with a 50 N load cell, to measure the shear load. The maximum shear load (N) was calculated based on the chip area (mm 2 The value obtained by dividing the measured value by the coefficient of friction coefficient was defined as the tack strength (kPa), and the average value of the measured values for eight laminates was taken as the tack strength.
[0131] (3) Die shear strength The bond strength of the bonded structure was evaluated based on the die shear strength between the silicon chip and the copper substrate bonded with the metal paste.
[0132] On the metal particle-containing layer formed in the same manner as in (1), a silicon chip (area 2 mm × 2 mm, thickness 400 μm, having a copper sputtered layer as the adhesion surface (bonding surface)) was mounted using a desktop manual die bonder (T-3000-FC3, manufactured by Dr. TRESKY) under conditions of room temperature of 25°C, load of 0.4 kg, and load application time of 1 second to obtain a laminate.
[0133] The obtained laminate was placed in a bonding device (manufactured by Ayumi Industries Co., Ltd.), and the pressure was reduced to 13 Pa to remove the air, after which nitrogen gas was introduced and replaced, and while flowing nitrogen at normal pressure at 10 L / min, the device was heated at 260°C and 10 MPa for 5 minutes to obtain a bonded body in which the copper plate and silicon chip were bonded with the copper sintered body. This bonded body was cooled, and when it reached 50°C or less, it was taken out into the air.
[0134] The silicon chip of the resulting bonded body was pressed horizontally at a measurement speed of 100 μm / s and a measurement height of 100 μm using a universal bond tester (STELLAR4000, manufactured by Nordson Corp.) equipped with a 1 kN load cell, to measure the shear load. The maximum shear load (N) was calculated based on the chip area (mm 2 The value obtained by dividing the bond strength by the bond strength was defined as the die shear strength (MPa), and the average value of the values measured for 11 bonded specimens was taken as the die shear strength.
[0135] [Preparation of Group A Compounds, Group B Compounds, and Group C Compounds] The compounds in the following table were prepared as group A compounds, group B compounds, and group C compounds.
[0136] [Table 1]
[0137] Details of the following compounds listed in Table 1 are as follows: Tetraethylene glycol: Polyethylene glycol 200 (hereinafter abbreviated as PEG200) (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., Polyethylene glycol 200) Isobornylcyclohexanol: Tersolve MTPH (Tersolve MTPH, manufactured by Nippon Terpene Chemical Co., Ltd.) Dihydroterpineol: Dihydroterpineol (hereinafter abbreviated as DHT) (manufactured by Nippon Terpene Chemical Co., Ltd., dihydroterpineol) Terpineol: α-terpineol (Terpineol C, manufactured by Nippon Terpene Chemical Co., Ltd.)
[0138] [Preparation of metal paste] The metal pastes were prepared according to the procedure described below in the amounts (parts by mass) shown in Table 1. The amounts shown in the table are the ratios (parts by mass) of each component when the total mass of the metal paste is 100 parts by mass.
[0139] Example 1 PEG200 was prepared as the compound in group A, DHT as the compound in group B, and lauric acid as the compound in group C. As a liquid dispersion medium, 50 g of PEG200, 140 g of DHT, and 10 g of lauric acid were mixed. 560 g of CH-0200L1 (product name of Mitsui Mining & Smelting Co., Ltd., laser scattering method 50% volume average particle size 0.2 μm) as submicro copper particles, 120 g of Cu-HWQ1.5 μm (product name of Fukuda Metal Foil & Powder Co., Ltd., laser scattering method 50% volume average particle size 1.5 μm) as spherical micro copper particles, and 120 g of ST-Cu-325 (product name of Yamaishi Metal Co., Ltd., laser scattering method 50% volume average particle size 30 μm) as flake-shaped micro copper particles were mixed with this mixed dispersion medium.
[0140] The resulting mixture was stirred for 30 minutes at 300 rpm using a planetary mixer (manufactured by Primix Co., Ltd.). This was dispersed once using a dispersizer (manufactured by Shinto Kogyo Co., Ltd.) under conditions of a gap of 50 μm and a rotation speed of 12,000 rpm to obtain a slurry. The mixture was then stirred for 3 minutes at 2,000 rpm under reduced pressure using a planetary mixer (manufactured by Thinky, Awatori Rentaro ARE-310) to obtain a metal paste of 80 mass%.
[0141] (Examples 2 to 4) A metal paste was obtained in the same manner as in Example 1, except that the compound in group A was changed to the compound shown in Table 2 instead of PEG200.
[0142] (Examples 5 to 8) A metal paste was obtained in the same manner as in Example 1, except that the compound in group B was changed to a compound shown in Table 3 instead of DHT.
[0143] (Examples 9 to 12) A metal paste was obtained in the same manner as in Example 1, except that the compound in Group C was changed to a compound shown in Table 4 instead of lauric acid.
[0144] (Comparative Examples 1 to 3) A metal paste was obtained in the same manner as in Example 1, except that the compound in group A was changed to the compound shown in Table 5 instead of PEG200.
[0145] Comparative Example 4 A metal paste was obtained in the same manner as in Example 1, except that the compound in Group C was changed to a compound shown in Table 5 instead of lauric acid.
[0146] The metal pastes obtained in the examples and comparative examples were used to carry out the above evaluations (1) to (3).
[0147] [Table 2]
[0148] [Table 3]
[0149] [Table 4]
[0150] [Table 5]
Claims
1. A first step of applying a metal paste containing metal particles and a liquid dispersion medium that is liquid at 25° C. onto a first member to form a coating film of the metal paste; a second step of removing a portion of the liquid dispersion medium from the coating to form a metal particle-containing layer; a third step of disposing a second member on the metal particle-containing layer to obtain a laminate; a fourth step of sintering the metal particle-containing layer of the laminate; Equipped with In the second step, droplets are generated on the surface of the metal particle-containing layer.
2. the liquid dispersion medium contains a first compound and a second compound having a lower boiling point and a smaller SP value than the first compound, The method for producing a joint body according to claim 1 , wherein the metal paste contains a third compound having a smaller SP value than the second compound.
3. the liquid dispersion medium contains a polyether alcohol-based compound and an alcohol-based compound having a boiling point lower than that of the polyether alcohol-based compound and having a hydrocarbon group having 8 or more carbon atoms; The method for producing a joint body according to claim 1 , wherein the metal paste contains a fatty acid having 10 or more carbon atoms.
4. The method for producing a joined body according to any one of claims 1 to 3, wherein the metal particles contain submicro copper particles, spherical micro copper particles, and flake-shaped micro copper particles.
5. The method for producing a bonded body according to any one of claims 1 to 3, wherein at least one of the first member and the second member is a semiconductor element.
6. 4. The method for producing a joint body according to claim 1, wherein a ratio of a total area of the droplets to a surface of the metal particle-containing layer is 3 to 50%.
7. A metal paste comprising metal particles and a liquid dispersion medium that is liquid at 25°C, the liquid dispersion medium contains a first compound and a second compound having a lower boiling point and a smaller SP value than the first compound, The metal paste contains a third compound having a smaller SP value than the second compound.
8. A metal paste comprising metal particles and a liquid dispersion medium that is liquid at 25°C, the liquid dispersion medium contains a polyether alcohol-based compound and an alcohol-based compound having a boiling point lower than that of the polyether alcohol-based compound and having a hydrocarbon group having 8 or more carbon atoms; The metal paste contains a fatty acid having 10 or more carbon atoms.
9. The metal paste according to claim 7 or 8, wherein the metal particles include sub-micro copper particles, spherical micro copper particles, and flake-shaped micro copper particles.
10. A method for producing a metal paste, comprising the steps of: preparing at least a first compound that is liquid at 25°C; a second compound that is liquid at 25°C and has a lower boiling point and a smaller SP value than the first compound; a third compound that is liquid at 25°C and has a smaller SP value than the second compound; and metal particles; and preparing a dispersion liquid containing the first compound, the second compound, the third compound, and the metal particles.
11. A method for producing a metal paste, comprising the steps of: preparing at least a polyether alcohol-based compound that is liquid at 25°C; an alcohol-based compound that is liquid at 25°C and has a boiling point lower than that of the polyether alcohol-based compound and has a hydrocarbon group having 8 or more carbon atoms; a fatty acid having 10 or more carbon atoms; and metal particles; and preparing a dispersion liquid containing the polyether alcohol-based compound, the alcohol-based compound, the fatty acid, and the metal particles.
12. The method for producing a metal paste according to claim 10 or 11, wherein sub-micro copper particles, spherical micro copper particles, and flake-shaped micro copper particles are prepared as the metal particles.
13. A metal-pasted member comprising: a member; and a coating film of the metal paste according to claim 7 or 8 provided on the member.
Citation Information
Patent Citations
JP1975006081A
Cited By
Bonding paste composition, method for producing bonded structure, method for temporarily fixing to-be-bonded body, and bonded structure
WO2026205244A1